2005
DOI: 10.7202/706232ar
|View full text |Cite
|
Sign up to set email alerts
|

Green foxtail (Setaria viridis) resistance to acetolactate synthase inhibitors

Abstract: Des sétaires vertes (Setaria viridis) présumées résistantes aux inhibiteurs de l'acétolactate synthase (ALS) ont été identifiées en 1999 au Wisconsin, É.-U., dans un champ de soja (Glycine max) issu d'un semis direct. La résistance aux herbicides imidazolinone et sulfonylurée a été caractérisée au niveau de la plante entière et de celui des enzymes. Ces sétaires vertes au stade trois à quatre feuilles étaient respectivement 1020, 53 et 6,5 fois plus résistantes à l'imazethapyr, à l'imazamox et au nicosulfuron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The results of this study revealed that although all fluridone-resistant hydrilla biotypes behaved differently in response to fluridone concentrations over time, EC 50 values for phytoene and b-carotene content followed almost identical trends in response to varying fluridone concentrations in all biotypes. Factors that accelerate the selection of resistant biotypes include repeated use of a single herbicide in large areas, the failure to alternate different modes of action, and long residual herbicide activity (Maxwell and Mortimer 1994;Volenberg et al 2002). Fluridone has been the primary herbicide used in hydrilla control programs in Florida for over two decades.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study revealed that although all fluridone-resistant hydrilla biotypes behaved differently in response to fluridone concentrations over time, EC 50 values for phytoene and b-carotene content followed almost identical trends in response to varying fluridone concentrations in all biotypes. Factors that accelerate the selection of resistant biotypes include repeated use of a single herbicide in large areas, the failure to alternate different modes of action, and long residual herbicide activity (Maxwell and Mortimer 1994;Volenberg et al 2002). Fluridone has been the primary herbicide used in hydrilla control programs in Florida for over two decades.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that some herbicides can have initial phytotoxic effects, although seedlings usually recover without severe damage, and yield loss are not observed (Díaz et al 1992;Ivany et al 2002;Thomas et al 1994;Tonks et al 1991;Volenberg et al 2002;Young et al 2003). In other studies, however, various clover species were exposed and evaluated for tolerance to different herbicides including pendimethalin and metolachlor (Tharp and Kells 2000), bentazon and 2,4-D (Evers et al 1993), 2,4-D and dicamba (Griffin et al 1984), and MCPA and 2,4-DB (Conrad and Stritzke 1980); in all cases, yield and persistence of the legume were markedly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…As an example see the results for a study in which the untreated control of two Setaria viridis (green foxtail) populations had similar shoot biomass but produced different biomass at the highest dose of imazethapyr or imazamox. 21 This situation can be compared to a competition between two downhill skiers where they start at the same altitude (similar upper limit u) but finish at different altitudes. Again, it makes no sense to compare the time to reach the midway point (relative ED 50 in a dose-response context) as the end points differ.…”
Section: Error #2: Comparing Ed 50 Values and Calculating The Ri Of Nonparalleled Curvesmentioning
confidence: 99%